Two Challenge and Rechallenge Episodes of Chloroquine-Induced Psychotic Mania in a Patient with Rheumatoid Arthritis - Plesnicar, B. K.; Velikonja, I.; Plesnicar, A.; Vitorovic, S. (Aktuelle Rheumatologie, 2013)
Chloroquine, an anti-malarial drug, is also used in the treatment of rheumatoid arthritis. It has been known for decades that chloroquine could cause psychiatric side effects; however, reports are scarce. This report concerns a rare case of 2 challenge and re-challenge episodes of mania during chloroquine treatment of rheumatoid arthritis. Some hypothetical pathophysiological mechanisms that may lead to these adverse effects are discussed.
Keywords: chloroquine; rheumatoid arthritis; psychotic mania